Dynamics Of An Advocate From A Syariah Scholar - Agung Taufik Wahyuda; Fauhan Thirafi; Siti Arawiyyah Ardi; Rini Fadilla Tunnisa Harahap (Sean Institute, 2024)
Sharia graduates have very broad opportunities when becoming advocates. However, if we look at the reality that even though the law has provided opportunities for sharia graduates, very few of them become advocates. The method applied in this study is an empirical method in the field of law, namely a method that considers the reality that exists in field practice. Despite many obstacles, sharia graduates are still very much needed today. They have different predicates and are expected to contribute to law enforcement. Their existence can bring enlightenment to weak laws and corruption. However, the sharia faculty